Characterization of Bilateral Parietal Thinning. Issue 3 (May 2020) - Sanati-Mehrizy, Paymon; Graziano, Francis D.; Naidich, Thomas; Taub, Peter J.
Abstract : Background: Bilateral parietal thinning (BPT) of the calvarium is uncommon but can lead to significant morbidity, including pain or communication through the thinned bone. This study aimed to define and characterize a novel grading system for BPT. Methods: Coronal CT scans of patients with BPT were retrospectively analyzed and anatomic measurements were taken including (1) thinning ratio, defined as calvarial thickness at the thinnest point divided by the average thickness of the surrounding bone and (2) width of the defect. In addition, patient demographics and comorbidities were collected. Results: Forty-three patients were identified with BPT, with an average age of 73 ± 16 years and 74% were female. The authors' novel grading scheme based on depth of calvarium involvement was found to be significantly correlated to thinning ratio ( P < 0.001) and width ( P < 0.001). When controlling for comorbidities, increasing age ( P = 0.044) was the only significant independent risk factor associated with thinning ratio. With respect to defect size, when controlling for comorbidities, both hypertension ( P = 0.025) and increasing age ( P = 0.024) were found to be significant independent risk factors related to increasing defect size. Twenty patients (47%) had multiple CT scans (range 5 month–5 year interval). In this group, patients had an average of 0.66 ± 0.11 mm decrease in parietal thickness per each year of increasing age, showing progressive parietal thinning with time. Conclusion: This study proposes a novel quantitatively-characterized grading scheme for BPT. The authors' results indicate that when controlling for comorbidities, BPT thinning is associated with increasing age, while defect width is associated with increasing age and hypertension. This grading scheme can help to diagnose, classify, and monitor patients with parietal bone thinning. Abstract : Supplemental Digital Content is available in the text